Re-traumatization in Saadat Hassan Manto’s Black Borders: A Trauma Study - Rai, Bidur (Gyanjyoti, 2023)
The research article analyzes the re-traumatization of the victimized and the survivors in the partition violence in Saadat Hassan Manto’s “Black Borders”, portraying the trauma of war and the conflicts of the residents. Its purpose is to show how the victims get traumatized through the literary text of the partition and to evaluate the atrocities in the history of the partition riots and huge holocaust. This vignette describes the unspeakable scales of reports of the riots of a culturally diverse people. They cannot safeguard the culture of that society, their beliefs, perceptions, values, and cultural ideology. These people are compelled to either remain faithful to the legacy of previous generation or choose their own destiny. A number of people formulate the worldviews in the case of the partition violence to accept the incident as an aberration. A valid philosophy of the partition is that it creates the shift in the cultural, political, and economic position of the nations. To interpret the text, the paper writer embraces the perspectives of Trauma and memory devices as a theoretical framework. For this matter, the perspectives of Cathy Caruth, Jennifer Yusin, Gyanendra Pandey, and Stefano Bianchini have been used. Since partition violent atrocities displace and deprive the people of the freedom and a choice, this article examines the experiences of the traumatized characters. The study concludes the significant role of the partition literature in helping the people to resolve their psychological disorder resulted due to the violence.